Explaining cross-national variation in workplace employee representation. (December 2017) - Forth, John; Bryson, Alex; George, Anitha
Debates on the desirability of workplace employee representation are rarely evidence based. We use a workplace survey covering 27 EU countries to show that its incidence is strongly and independently correlated with the degree of centralization in a country's industrial relations regime and the extent of legislative support. Industry profits are important in explaining trade union presence but are unimportant in the case of works councils. We find support for the exit-voice model, traditionally associated with Anglophone regimes, whereby worker representation is associated with poorer perceptions of the employment relations climate and with lower voluntary quit rates.